2007
DOI: 10.1182/blood.v110.11.2483.2483
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Oligo-Clonal Usage of Monoclonal Immunoglobulin λ Light Chain Germline in POEMS Syndrome.

Abstract: Background: POEMS syndrome (also known as Crow-Fukase or Takatsuki syndrome) is a rare plasma cell disorder characterized by peripheral neuropathy, a monoclonal plasma cell disorder, and other paraneoplastic features including organomegaly, endocrinopathy, skin changes, edema and effusions. High levels of vascular endothelial growth factor (VEGF) in the serum may contribute to pathology seen in this disease but exact pathogenetic mechanisms are still unclear. A unique feature of this syndrome is that the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“… 18 The V-region of the Ig lambda gene interested was limited to the V lambda 1 subfamily (IGLV1). 8 , 19 Kang et al reported in 20 newly diagnosed POEMS cytogenetic aberrations similar to other plasma cell dyscrasias, but with a different incidence. 20 In particular, 14q32 (IGH) translocation was observed in 45% of the cases and included the t(4;14) and t(11;14) translocation (15% and 25% of the cases, respectively).…”
Section: Mandatory Criteriamentioning
confidence: 99%
“… 18 The V-region of the Ig lambda gene interested was limited to the V lambda 1 subfamily (IGLV1). 8 , 19 Kang et al reported in 20 newly diagnosed POEMS cytogenetic aberrations similar to other plasma cell dyscrasias, but with a different incidence. 20 In particular, 14q32 (IGH) translocation was observed in 45% of the cases and included the t(4;14) and t(11;14) translocation (15% and 25% of the cases, respectively).…”
Section: Mandatory Criteriamentioning
confidence: 99%
“…IL‐12 has also been shown to correlate with disease activity . Little is known about the plasma cells in POEMS syndrome except that more than 95% of the time they are lambda light chain restricted with restricted immunoglobulin light chain variable gene usage . Translocations and deletion of chromosome 13 have been described .…”
Section: Disease Overviewmentioning
confidence: 99%
“…IL‐12 has also been shown to correlate with disease activity . Little is known about the plasma cells in POEMS syndrome except that more than 95% of the time they are lambda light chain restricted with restricted immunoglobulin light chain variable gene usage (IGLV1) . Translocations and deletion of chromosome 13 have been described, but hyperdiploidy is not seen …”
Section: Disease Overviewmentioning
confidence: 99%